Pemberdayaan Masyarakat Dukuh Wates dalam Pemanfaatan TOGA pada Era Komunikasi Global - Nizar Nauli Sinangkling; Dhevi Anastia Richakza Indrajatun; Fernanda Frisky Warhandika; Harun Joko Prayitno (Universitas Pendidikan Muhammadiyah Sorong, 2022)
TOGA or Family Medicinal Plant is one of the cultivated plants that can be carried out in the yard area of the house where it can be utilized and used as medicine. Due to the lack of use of TOGA as a natural breakthrough in maintaining the immune system among the community, this will have an impact on the addition of positive cases of the COVID-19 virus that occurred in Indonesia. So that efforts can be made to the community, namely providing empowerment regarding the use of TOGA or Family Medicinal Plants which are used as Immunomodulator agents. The purpose of the research in this article is to increase the use of TOGA or Family Medicinal Plants as a form of effort to maintain the body's immune system in the era of adaptation to new habits. Where in this study is concerned with the people of Hamlet Wates, RT 20/RW 03, Lencoh Village, Selo District, Boyolali Regency which includes 48 families. The method used in this research includes several things, namely public education by conducting counseling; training with the community by conducting demonstrations; and Diffusion of Science and Technology by producing processed products from the use of TOGA. Then from the research, it was found that after empowering the local community, the community was more aware of various kinds of medicinal plants and how to properly use medicinal plants into herbal ingredients that can be consumed every day to maintain the body's immune system.